2001
DOI: 10.1097/00043764-200110000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Falls in the US Construction Industry, 1990 to 1999

Abstract: The Occupational Safety and Health Administration's (OSHA's) Integrated Management Information System (IMIS) database allows for the detailed analysis of risk factors surrounding fatal occupational events. This study used IMIS data to (1) perform a risk factor analysis of fatal construction falls, and (2) assess the impact of the February 1995 29 CFR Part 1926 Subpart M OSHA fall protection regulations for construction by calculating trends in fatal fall rates. In addition, IMIS data on fatal construction fall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 12 publications
1
49
0
Order By: Relevance
“…The construction industry continues to be one of the most hazardous industries in terms of serious injuries, lost working time ( Dong et al , 1995 ;Brenner and Ahern, 2000 ;Derr et al , 2001 ), hospitalization ( Spangenberg et al , 2005a ), disability ( Hannerz et al , 2005 ) and mortality ( T ü chsen et al , 2005 ) and there is a great need to improve occupational safety and Spangenberg health of the employees. In general, there are three main areas in the construction industry: building construction, rail and road construction, and industrial construction.…”
Section: Setting the Stagementioning
confidence: 99%
“…The construction industry continues to be one of the most hazardous industries in terms of serious injuries, lost working time ( Dong et al , 1995 ;Brenner and Ahern, 2000 ;Derr et al , 2001 ), hospitalization ( Spangenberg et al , 2005a ), disability ( Hannerz et al , 2005 ) and mortality ( T ü chsen et al , 2005 ) and there is a great need to improve occupational safety and Spangenberg health of the employees. In general, there are three main areas in the construction industry: building construction, rail and road construction, and industrial construction.…”
Section: Setting the Stagementioning
confidence: 99%
“…Derr et al (2001) identified that the number of fatal accidents has increased because of falls on the construction site in different subsectors. Also, in the US most accidents are falls from height (Huang and Hinze, 2003;Schaufelberger and Lin, 2014).…”
Section: Falls Accidents and Injuriesmentioning
confidence: 99%
“…Prevention strategies against injuries are many and different [6,7,10,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. The meta-analysis results indicate that data relating to fatal injuries show a progressive and constant decrease over a medium-to long-term period.…”
Section: Key Pointsmentioning
confidence: 99%
“…Epidemiological data show that while these interventions are able to reduce the number of injuries in construction, their rate still remains very high [6][7][8].…”
Section: Introductionmentioning
confidence: 99%